Immediate human pulp response to ethanol-wet bonding technique. Issue 5 (May 2015) - Salles Scheffel, Débora Lopes; Sacono, Nancy Tomoko; Dias Ribeiro, Ana Paula; Soares, Diana Gabriela; Basso, Fernanda Gonçalves; Pashley, David; de Souza Costa, Carlos Alberto; Hebling, Josimeri
Abstract: Objectives: To evaluate the short-term response of human pulps to ethanol-wet bonding technique. Methods: Deep class V cavities were prepared on 17 sound premolars and divided into three groups. After acid-etching, the cavities from groups 1 (G1) and 2 (G2) were filled with 100% ethanol or distilled water, respectively, for 60 s before the application of Single Bond 2. In group 3 (G3, control), the cavity floor was lined with calcium hydroxide before etching and bonding. All cavities were restored with resin composite. Two teeth were used as intact control. The teeth were extracted 48 h after the clinical procedures. From each tooth serial sections were obtained and stained with haematoxylin and eosin (H/E) and Masson's trichrome. Bacteria microleakage was assessed using Brown & Brenn. All sections were blindly evaluated for five histological features. Results: Mean remaining dentine thickness was 463 ± 65 μm (G1); 425 ± 184 μm (G2); and 348 ± 194 μm (G3). Similar pulp reactions followed ethanol- or water-wet bonding techniques. Slight inflammatory responses and disruption of the odontoblast layer related to the cavity floor were seen in all groups. Stained bacteria were not detected in any cavities. Normal pulp tissue was observed in G3 except for one case. Conclusions: After 48 h, ethanol-wet bonding does not increase pulpal damage compared to water-wet bonding technique. Clinical significance: Ethanol-wet bonding may increase resin-dentine bond durability. This study reported the in vivo response of human pulp tissue when 100% ethanol was applied previously to an etch-and-rinse simplified adhesive system.